Respuestas institucionales sobre las urbanizaciones informales en los cerros de Bogotá (2017)
This thesis consist of four chapters that present a conceptual approach to informal urban processes, which are informal urban processes, which have been the institutional responses to these processes, and what has been the perception of citizenship in the light of The zones of Pardo Rubio and Verbenal located on the slopes of the eastern hills and on the urban and environmental limits of the city of Bogotá. Based on the comparative case study methodology, with research methods such as structured interviews - a portion of the zonal units - and semi-structured interviews with experts, as well as a review of secondary bibliographic sources, this research aims to understand the responses Institutions of the UPZ Pardo Rubio and Verbenal. Viewed mainly from the theoretical perspective of Joan Prats about the concept of governability - the capacity of the State to respond to the demands of citizenship through policies - and Brenner's critique of the urban critique theory, this study had to research the causes and implications of informal urban processes in the city of Bogotá, problematizes the failures that have presented the institutional responses provided by the State, and incurs the exploration of issues about the perception of the citizenship on the institutional responses implemented in Pardo Rubio and Verbenal. One of the main conclusions of the actual investigation is that the State, despite its efforts to understand the logic of informal urban processes, has had difficulty in identifying and recognizing different development logics than those provided by urban formality.